Síndrome de Burnout en personal administrativo y aprendices de una empresa privada de la ciudad de Ciénaga, Magdalena (2023)
The study of Burnout Syndrome has been growing since the 20th century and intensified after the COVID-19 pandemic and the current world mental health crisis. The main objective of this study is to analyze the level of occupational burnout in the administrative personnel and apprentices of a private company in the municipality of Ciénaga, Magdalena. The methodology used was quantitative and the design was descriptive. A sample of 34 participants was used, distributed among administrative personnel and apprentices of the private entity. The questionnaire applied was the Occupational Attrition Scale with a duration of 20-30 for each person evaluated. The data analysis was carried out using Microsoft Excel. The results of the research affirm that high and very high levels of occupational burnout are present in both trainees and administrators; people who identify with the positive gender have higher levels of emotional burnout than men.